Building a sustainable food future since 1967: Fifty years and 50 wins - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2017)
When CIAT was created In 1967, the majority of poor and hungry people in the tropics were smallholder farmers. Increasing the productivity of their crops was, therefore, the critical entry point for CIAT’s research. Since that time, we have been concerned with nearly every aspect of tropical agriculture: the crop varieties that farmers grow, the production systems they manage, the agricultural landscapes they inhabit, the markets in which they participate, and the policies that influence their options and decisions. On the occasion of our 50th Anniversary, we are happy and proud to share a selection of “50 wins” in the fight against hunger, malnutrition and poverty, and towards a sustainable food future.